Targeting the Wnt Pathway in Cancer - Goss, Kathleen H.; Kahn, Michael (Springer New York : Imprint: Springer, 2011)
The Wnt pathway is an evolutionarily conserved signaling network that is critical for mammalian development and adult tissue maintenance, and, importantly, hyperactivated in most human cancers. Almost two decades of study has confirmed that Wnt signaling is necessary and sufficient for cancer pathogenesis in multiple in vitro and in vivo models systems, suggesting that the pathway represents an attractive therapeutic target.  Recent efforts have focused on innovative strategies to antagonize Wnt signaling at various levels of the pathway - from attenuating the extracellular signaling through the Wnt receptors to modulating the catenin destruction complex to blocking catenin-mediated transcription. Many of these approaches have been largely successful in preclinical validation studies and have been met with considerable enthusiasm to move forward into clinical trials. In this book, we highlight the recent advances in our understanding of the complexity of the Wnt pathway, particularly its intricate regulation and cross-talk with other key signal transduction pathways in normal and tumor cells. As a way to comprehend the role of Wnt pathway activation in tumor initiation and progression, we discuss the importance of Wnt signaling in embryonic and tissue development and stem cell maintenance and self-renewal. The evidence for aberrant Wnt pathway activation in human solid and hematopoietic cancers, as well as a few of the genetic mouse models that mimic the Wnt pathway deregulation observed in some of these tumor types, is reviewed. Lastly, we summarize the current status of the development of Wnt pathway inhibitors, their efficacy in preclinical models and their potential as therapeutic agents for cancer. It is an exciting time in the Wnt signaling field - one that represents a key crossroad between dissecting the molecular details of the pathway and translating that work into promising targeted tumor therapies - that is likely to profoundly impact this research area for years to come.